Comparison of Nuclear Matrix Protein-22 and Urine Cytology in Diagnosing Bladder Cancer - Soedarso, Mohamad Adi; Wahyuni, YinYin; Tjahjati, Maria Immaculata (Indonesian Journal of Cancer, 2018)
Background: Urine cytology (UC) is a classic marker used to detect bladder malignancy through urine examination microscopically at the presence of malignant transitional cells that are released. UC  is also used to evaluate recurrence after past treatment. A new method that is simpler, faster and easier is by measuring protein in urine produced by malignant cells, namely nuclear matrix protein-22 (NMP-22). The aim of this study was to compare the diagnostic value of NMP-22 and UC to histopathological biopsy in diagnosing bladder carcinoma and to evaluate whether the NMP-22 test could be used for bladder carcinoma screening and recurrence monitoring.Methods: Diagnostic tests on 24 suspected bladder malignancies were performed by taking urine samples for NMP22 examination and UC. Sensitivity, specificity, positive predictive value and negative NMP-22 and UC on histopathological biopsy were analyzed.Results: Positive results were obtained in 21 (87.5%) and negative in 3 (12.5%) NMP22 examinations. The sensitivity, specificity, positive and negative predictive values of NMP-22 on histopathological biopsy were 95%; 67%, 95%, 67%. Sensitivity, specificity,positive predictive value and negative UC on histopathological biopsy were 38.1%; 100%, 100%, 18.8%.Conclusions: NMP-22 sensitivity is higher than UC in diagnosing bladder carcinoma. NMP-22 can be used for bladder carcinoma screening and for recurrence monitoring